Visualization of License Plate Recognition System - Zhiyi Ruan; Ying Zou; Dongming Hong; Lurong Wu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The image of the license plate is located and segmented by some digital-image processing technologies such as gray-scale processing, gray-scale stretching and filtering, edge detection, morphological processing, Hough transformation etc. According to the characteristics of the license plate, binary matrix of character image sets the fuzzy matrix, and based on the principle of proximity computing space of closeness to get the fuzzy pattern recognition of characters. On the basis of the data of image pixels, the samples which are randomly selected under noisy condition and which are treated by morphological processing are randomly selected, and then the samples are used to test the simulation and identification of Back Propagation (BP) Neural Networks. With the mathematical software-Matlab programming, the license plates are recognized. The aim is to develop the Visualization of user interface in License Plate Recognition System. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3520